Shaping employee excellence: The influence of leadership, work environment, and motivation on discipline and performance at puskesmas in Palangka Raya - Harjoni, Harjoni (JSM: Jurnal Sains Manajemen, 2024)
The objective of this investigation is to examine the direct and indirect effects of leadership, work environment, and work motivation on the work discipline and performance of employees within Health Care Centers located in Kota Palangka Raya. The analytical framework employed is path analysis, which aims to identify the variables that exert the most significant influence on work discipline and performance, thereby facilitating future planning to enhance health service delivery within the community. The research methodology involves establishing causal relationships between variables, with AMOS Version 16 utilized as the analytical tool. Subsequently, validity and reliability assessments are conducted within the context of the measurement model, employing Confirmatory Factor Analysis (CFA). The aim is to ascertain whether latent variables (leadership, work environment, work motivation, work discipline, and performance) along with their respective factor items (indicators or manifestation variables) can adequately elucidate a construct. Should a relationship be identified, the model is deemed “FIT,” permitting further analysis, specifically the structural model test, which is conducted on a sample of 170 health center employees randomly selected from across the city of Palangka Raya, encompassing both medical personnel and administrative staff. The outcomes of the measurement model evaluation, grounded in the model itself, the sample size, and the available data, indicate that the model is appropriate (fit), with the variables (leadership, work environment, work motivation, work discipline, and performance) and indicators demonstrating significance (valid and reliable). Furthermore, structural model testing, based on normality and outlier analysis, confirms that the data is normally distributed without the presence of outliers, and the construct exhibits significance with a loading factor exceeding 0.60